Annual Plan, 1970-71 Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1970)
Since liberation 1961 the Territory, of Goa, Daman and Diu has been experiencing stresses and strains normal in the transitional stags. The problem faced immediately after the liberation was the integration of the Region with the rent of the country economically. The Territory comprises of 3 land blocks separated from each other by a distance of over 300 miles. The Territory covers an area of 3706 sq. m. of which. 97.4$ is in Goa and Daman and Diu account for 57 and 38 sq.m., respectively. The population of the Territory was 626667 in 19fil Census and was estimated 643500 in 1966. This population lives in 13 towns and 247 villages.
Planning Commission Programme Administration Division
Planning Commission Programme Administration Division